2006
DOI: 10.1002/ppul.20408
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of apparent life‐threatening events in infants with esophageal atresia

Abstract: Many infants with a repaired esophageal atresia (EA) undergo fundoplication, aortopexy, or glossopexy because the mechanisms most responsible for airway obstruction and/or apparent life-threatening event (AO/ALTE) syndrome are considered to be gastroesophageal reflux (GER), tracheal compression (TC), or obstructive apnea, respectively. In the present study, we investigated whether these mechanisms are independent or interrelated. We developed a database of 120 consecutive patients with EA treated by the senior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…32 Less frequent are RTIs, wheezing, and cough; these findings mainly are derived from studies using a cross-sectional design. [33][34][35][36] showed that 41% of adolescents after repair of EA still had respiratory symptoms, and 52% had ever had pneumonia or wheezing.…”
Section: Discussionmentioning
confidence: 99%
“…32 Less frequent are RTIs, wheezing, and cough; these findings mainly are derived from studies using a cross-sectional design. [33][34][35][36] showed that 41% of adolescents after repair of EA still had respiratory symptoms, and 52% had ever had pneumonia or wheezing.…”
Section: Discussionmentioning
confidence: 99%
“…One or more of these dysautonomic features are found in nearly all patients with esophageal atresia [1][2][3], suggesting that autonomic disturbances and esophageal atresia may be manifestations of maldevelopment of cephalic neural crest derivates (neurocristopathy) [3]. This theory is supported by the findings that about three fourths of patients with esophageal atresia, such as the present patients with asymmetric sweating and/or flushing, present a neural crest related cardiovascular anomaly [11] and an asymmetric facial defect [3].…”
Section: Discussionmentioning
confidence: 65%
“…We reviewed the hospital records of patients consecutively admitted between January 2003 and December 2007 to update the database used in a previous study [2]. In our database, flushing was not coded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may suffer apneic spells (72,73) or barking cough (74) during infancy and childhood, frequent vomiting (75), repeated pneumonia (69,76,77) and/or chronic respiratory tract disease (78) that are considered as sequelae of the esophageal malformation but that might be related directly to the GER. Recurrent anastomotic strictures are indeed related to GER and become manageable after effective anti-reflux treatment (79).…”
Section: The Problem Of Associated Gastroesophageal Reflux (Ger)mentioning
confidence: 99%